Antibacterial Activity Test of Gambas Fruit Extract (Luffa Acutangula (L.) Roxb.) against Bacterial Growth Staphylococcus Aureus In Vitro - Stanlee, Elwin; Indra Basar Siregar; Olivia Avriyanti Hanafiah; Isnandar (HM Publisher, 2023)
One aspect that needs attention in dental and oral health is bacterial infection, including infections caused by Staphylococcus aureus bacteria. Staphylococcus aureus is a type of gram-positive bacteria that can be found in various parts of the human body, including the skin and nasal mucus. These bacteria usually do not cause problems if they remain within normal limits. However, when Staphylococcus aureus enters the oral cavity or surrounding tissue, it can cause various dental and oral health conditions. Gambas fruit (Luffa acutangula (L.) Roxb.), which is also known as Oyong fruit from the Cucurbitaceae family, has an antibacterial effect. This study aimed to determine the antibacterial activity of the ethanol extract of Gambas fruit (Luffa acutangula (l.) roxb.) on bacterial growth of Staphylococcus aureus in vitro. This type of research is a laboratory experimental design post-test only control group. Research data were analyzed using testone-way ANOVA with post-hoc LSD. The results showed that there was an inhibition diameter at each concentration of Gambas fruit extract. 25% Gambas fruit extract has an average diameter of 10.8 mm, 12.5% Gambas fruit extract has an average diameter of 9.4 mm, 6.25% Gambas fruit extract has an average diameter of 8 mm, l Gambas fruit extract 3.125% has an average diameter of 6.9 mm. Gambas fruit extract has antibacterial properties with a minimum inhibition level of 25% against the bacterial growth of Staphylococcus aureus.